Ecotoxicological effects of the azole antifungal agent clotrimazole on the macrophyte species Lemna minor and Lemna gibba - Alkimin, Gilberto Dias de (2022)
Pharmaceuticals are a large and diverse group of compounds used to treat, prevent and diagnose disease. Among these, a group that has been recently detected in the aquatic environment is that of the azole compounds, commonly used as antifungals. Clotrimazole (CLO) is a nonbiodegradable persistent azole compound, with broad-spectrum antifungal activity for which virtually no toxicological data are available, especially towards aquatic plants. The few existent data point to a documented interference with cytochrome P450 system of exposed organisms. Therefore, the aim of this paper was to evaluate the ecotoxicological effects of the fungicide CLO on two aquatic macrophyte species, namely, Lemna minor and Lemna gibba. To attain this purpose, an acute assay (96 h) was performed with both species being exposed to CLO, in a concentration range of 0 to 5 μg L-1. The analyzed endpoints were levels of chlorophyll a and b, total, carotenoids, catalase (CAT) and glutathione -s-transferases activities (GSTs). In general, CLO exposure caused some minor alterations in L. minor and L. gibba pigment contents. Antioxidant enzymes exhibited a different pattern in both species, since the highest concentrations of CLO caused an increase on CAT activity, and a decrease on GSTs activity in L. minor, and the opposite in L. gibba, reflected by a decrease on CAT activity and an increase on GSTs activity in all tested concentrations. These results demonstrate that CLO exposure resulted in potential deleterious effects on macrophytes, namely with the involvement of the antioxidant defense mechanisms that were likely deployed to cope with pro-oxidative conditions established by CLO.